Perceived job insecurity and well-being revisited: Towards conceptual clarity - Ingo Geishecker (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2009)
This paper analyzes the impact of job insecurity perceptions on individual well-being. While previous studies on the subject have used the concept of perceived job insecurity rather arbitrarily, the present analysis explicitly takes into account individual perceptions about both the likelihood and the potential costs of job loss. We demonstrate that any model assessing the impact of perceived job insecurity on individual well-being potentially suffers from simultaneity bias yielding upward-biased coefficients. When applying our concept of perceived job insecurity to concrete data from a large household panel survey we find the true unbiased effects of perceived job insecurity to be more than twice the size of estimates that ignore simultaneity. Accordingly, perceived job insecurity ranks as one of the most important factors in employee well-being and paradoxically can be even more harmful than actual job loss with subsequent unemployment.
Keywords: D84; J63; Z13; 330; job security; life satisfaction; unemployment; Arbeitsplatzsicherung; Arbeitslosigkeit; Risiko; Wahrnehmung; Zufriedenheit; Schätzung; Deutschland